2008
DOI: 10.1080/14616730802113612
|View full text |Cite
|
Sign up to set email alerts
|

Changes in maternal sensitivity across the first three years: are mothers from different attachment dyads differentially influenced by depressive symptomatology?

Abstract: Hierarchical linear modeling was used to describe longitudinal relations between maternal sensitivity and depressive symptomatology for mothers of children with differing attachment classifications at 36 months of child age using data from the NICHD Study of Early Child Care. Attachment during toddlerhood was assessed using a modified Strange Situation Paradigm developed by the MacArthur Working Group on Attachment. On average, maternal sensitivity increased longitudinally from 6 to 36 months for groups with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 46 publications
2
38
0
4
Order By: Relevance
“…In this relatively low-risk context, most mothers seem able to maintain their levels of sensitive support for children over time. The variation in the change of maternal sensitivity corroborates other studies based on the same sample that have indicated different patterns of change in maternal sensitivity for children of different attachment quality in the first three years (Mills-Koonce, Gariepy, Sutton, & Cox, 2008) or for mothers with different trajectories of depressive symptoms from infancy to age 7 (Campbell, Matestic, von Stauffenberg, Mohan, Kirchner, 2007). Because we controlled for maternal depression and maternal harshness at each time point, as well as other child and demographic characteristics, our delineation of the average trajectory of maternal sensitivity should be quite precise.…”
Section: Discussionsupporting
confidence: 88%
“…In this relatively low-risk context, most mothers seem able to maintain their levels of sensitive support for children over time. The variation in the change of maternal sensitivity corroborates other studies based on the same sample that have indicated different patterns of change in maternal sensitivity for children of different attachment quality in the first three years (Mills-Koonce, Gariepy, Sutton, & Cox, 2008) or for mothers with different trajectories of depressive symptoms from infancy to age 7 (Campbell, Matestic, von Stauffenberg, Mohan, Kirchner, 2007). Because we controlled for maternal depression and maternal harshness at each time point, as well as other child and demographic characteristics, our delineation of the average trajectory of maternal sensitivity should be quite precise.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, in dyads with a secure attachment history, maternal negative emotions did not predict observed parent behavior. An earlier study with the same sample found that the link between maternal depression and observed maternal sensitivity differed by attachment status during the preschool years (Mills-Koonce, Gariepy, Sutton, & Cox, 2008). Our results extend these findings by demonstrating early attachment security continues to moderate associations between mother's self-reported emotional state and their actual parenting behaviors in early adolescence.…”
Section: Discussionsupporting
confidence: 78%
“…Infants are also given fewer opportunities to experience repair following moments of disrupted engagement (Jameson et al, 1997). Such disruptions in the early mother-infant relationship may serve as a precursor to insecure infant attachment (Mills-Koonce et al, 2008; Stern, 1995), which has longitudinally been linked to numerous adverse developmental outcomes (Sroufe et al, 2005), including the cognitive, emotional, and behavioral outcomes described above. One recent study (Laurent and Ablow, 2013) documented that maternal brain responses were altered in women with PPD.…”
Section: Maternal Caregiving In Postpartum Depressionmentioning
confidence: 99%